Intertheory relations in the social sciences: criminology as a physics of the social? - McGuire, Michael R. (Criminological encounters, 2019)
Where should we position Criminology within the social sciences? Is it merely a ‘rendez-vous’ discipline, dependent for its insights and status upon more venerable foundational disciplines like economics or sociology? In this paper I argue for a more radical stance, one which situates it at the methodological core of such disciplines. I offer three arguments in support of this stance. First, criminology’s decisive role in shaping the emergence of social science. Second, the foundational insights it offers into the problem of social order - arguably the central challenge for social science. Third, the striking way that many explanations of contemporary social order appear to supervene upon criminological concepts and ideas. I conclude by suggesting that the function of criminology as a social science may be akin to what Comte and Quetelet once called a ‘social physics’.